المؤسسة العسكرية والعملية السياسية : دراسة في المنطلقات النظرية - دخان, نورالدين; حفيظي, نورالدين (جامعة الوادي University of Eloued, 2018)
الملخص: جاءت هذه الورقة البحثية لتسليط الضوء على دراسة موقع المؤسسة العسكرية في العملية السياسية في النقاشات النظرية، وذلك انطلاقا من رصد وتحليل المنطلقات المفاهيمية لهذه الورقة البحثية، ومن ذلك المؤسسة العسكرية، العلاقات المدنية-العسكرية، الظاهرة العسكرية، على اعتبار أن الإحاطة التامة بهذه المفاهيم يعني التحكم في الدراسة جيدا، في حين جاء المحور الثاني ليناقش الأدبيات الكلاسيكية في دراسة مكانة الجيوش في الحياة السياسية والذي سيتم التركيز فيه على دراستي "صمويل هانتنجتون" و"موريس جانووتيز" التي تعتبر أساس الأبحاث والنظريات المعاصرة، أما في ختام الدراسة فتناولنا النظريات الحديثة التي جاءت في ظل الانتقادات الموجهة للنظريات التقليدية، بعد أن شهدت العديد من دول الجنوب بعد استقلالها تدخل العسكر في الشؤون السياسية، وترسخ ما يعرف بالظاهرة العسكرية التي كان لها أثرا سلبيا على مخططات التنمية وعلى الاستقرار السياسي نتيجة الصراع على السلطة وغياب الأمن. Abstract: This paper is presented for the sake of shedding light on studying the military establishment's position within the political process throughout theoretical discussions. It starts from monitoring and analysing this paper's concepts such as: the military establishment, the civil-military relations, and the military phenomenon, because taking control over these concepts means the better control of the study. The second chapter is devoted for discussing the literary classics within the study of the armies' status in the political life, in which it focuses on "Samuel Huntington" and "Maurice Janowitz's" studies, which are considered as the basis of contemporary research and theories. Finally, in the third chapter, we address the modern theories that come after criticizing the traditional theories, because many Southern countries are witnessing military interventions in their political affairs, after getting their independence, which has led to the appearance of what is known as the military phenomenon, that has a negative impact on the development plans and the political stability, because of a struggle
The Military And The Political Process A Study In The Theoretical Premises
Keywords: المؤسسة العسكرية ; العلاقات المدنية العسكرية ; الظاهرة العسكرية ; العملية السياسية ; الجيش; military establishment ; civil military relations ; military phenomenon ; political process ; army